Pengaruh Korosi Tulangan Terhadap Panjang Penyaluran pada Beton - Widianti Sri Anjani; Eko Walujodjati (Jurnal Konstruksi, 2022)
Reinforced concrete is two materials consisting of reinforcing steel and concrete that are used together. Steel reinforcement must have the same adhesive stress as the concrete components that surround it so that there must be strong bond between the two materials. The reinforcement used must be in good condition and not corroded. The purpose of this study was to determine the ratio of bond strength based on the length of distribution between corrosion and non-corrosion reinforcement using 10 mm diameter steel reinforcement with plain reinforcement. The method used in this study is the experimental method (experiment) carried out at the Civil Engineering Laboratory. Corrosion of the reinforcement is carried out by means of the corrosion rate at open air temperature where the reinforcement is positioned to receive free air. In this study, 9 samples of specimens used corrosion reinforcement, and 9 samples of specimens used non-corroded reinforcement. The bond strength test is carried out by means of a pull-out test, in which the reinforcing steel is pulled out until slip occurs or cracks appear in the concrete. The average bond stress of corroded reinforcement with a channel length of 150 mm is 3.808 MPa while non-corroded reinforcement is 4.137 MPa. The average bond stress of corroded reinforcement with a channel length of 100 mm is 3.66 MPa while non-corroded reinforcement is 4.222 MPa. The average bond stress of corroded reinforcement with a channel length of 50 mm is 7.363 MPa while non-corroded reinforcement is 6.684 MPa. In the corrosion reinforcement there was a decrease in the length of distribution from 150 mm to 100 mm but there was an increase at 50 mm. While non-corroded reinforcement there was an increase in distribution length from 150 mm, 100 mm, up to 50 mm.